2006
DOI: 10.1029/2005gl024213
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 14CO2, CO, and SF6 as tracers for recently added fossil fuel CO2 in the atmosphere and implications for biological CO2 exchange

Abstract: [1] We use the nearly ideal tracer 14 CO 2 to estimate the fossil fuel CO 2 enhancement in boundary layer air at two sites in New England and Colorado. Improved D 14 C measurement precision of 1.6-2.6% provides fossil fuel CO 2 detection capability of 0.8-1.5 ppm. Using the indirect tracers CO and SF 6 , we obtain two additional independent estimates of the fossil fuel CO 2 component, and we assess the biases in these methods with respect to the 14 CO 2 -based estimates. The SF 6 -based estimates vary consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
368
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(380 citation statements)
references
References 17 publications
12
368
0
Order By: Relevance
“…Using flask measurements of 14 CO 2 , CO and SF 6 , Turnbull found that 14 CO 2 was the most appropriate of the three tracers, and found that 1 ppm of CO 2 added from fossil fuels caused a depletion of Δ 14 C by approximately 2.8‰ [13]. Another common sampling method is to use NaOH to absorb atmospheric CO 2 , but this method is more complicated and it can be difficult to collect CO 2 samples from a wide area [22] at the same time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using flask measurements of 14 CO 2 , CO and SF 6 , Turnbull found that 14 CO 2 was the most appropriate of the three tracers, and found that 1 ppm of CO 2 added from fossil fuels caused a depletion of Δ 14 C by approximately 2.8‰ [13]. Another common sampling method is to use NaOH to absorb atmospheric CO 2 , but this method is more complicated and it can be difficult to collect CO 2 samples from a wide area [22] at the same time.…”
mentioning
confidence: 99%
“…It showed an overall increasing trend that became more rapid during the last 5 years of research, but the extent to which this is caused by fossil fuel emissions could not be determined. Atmospheric 14 CO 2 is considered to be one of the most sensitive tracers for monitoring fossil fuel derived CO 2 [13].…”
mentioning
confidence: 99%
“…There are more complex approaches described in the literature (Turnbull et al 2006) where they do not neglect the 14 C/C ratio difference between regional biogenic CO 2 and the mean background CO 2 . However, due to the large heterogeneity of the biosphere, the mean 14 C/C ratio of the regional biogenic component is rather difficult to measure and reliable estimates for this required parameter were not available for the Debrecen region in the studied term.…”
Section: Resultsmentioning
confidence: 99%
“…Adding fossil fuel CO 2 to the atmosphere, therefore, leads not only to an increase in the CO 2 content of the atmosphere, but also to a decrease in the 14 C/ 12 C ratio in atmospheric CO 2 (Suess 1955). From a 14 CO 2 measurement at a polluted sampling site, for example, near the ground level on the continent, we can directly calculate the regional fossil fuel CO 2 surplus (recently added fossil fuel CO 2 amount in air) if the undisturbed background 14 CO 2 level is known (Levin et al 2003;Turnbull et al 2006;Riley et al 2008). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation